Socio-Economic Indicators and their Impact on Sustainable Economic Development: An In-depth Analysis of Egypt - Balbaa, Muhammad Eid (International Journal of Economics and Financial Issues, 2024)
This research paper investigates the sophisticated relationship between socio-economic indicators and sustainable economic development in Egypt, employing a Linear Regression Model to provide an accurate analysis. Focusing on key variables such as Population, Life Expectancy at Birth, and Labor Force, the study seeks to discern their impact on Gross Domestic Product (GDP). With R Square of 0.9443, the model exhibits strong explanatory power. Noteworthy coefficients include a positive relationship between Population and GDP (β = $9,302.27), a negative relationship between Life Expectancy at Birth and GDP (β = -$45.77 Bln), and a positive relationship between Labor Force and GDP (β = $10,097.49). These findings contribute subtle insights to the literature and offer policymakers valuable information for fostering sustainable economic development in Egypt.